Capturing threshold responses of marine benthos along gradients of natural and anthropogenic change - Couce, Elena; Engelhard, Georg H.; Schratzberger, Michaela; Pinto, Rute (The Journal of applied ecology, 2020)
Ecologists and managers need to understand what types of communities emerge with continued human alterations to ecosystems against a background of natural change. Both natural and anthropogenic drivers are well known to affect organisms’ distributions; however, it often remains unclear where along a range of environmental and anthropogenic gradients important compositional community changes occur. We used a big‐data approach, including over 175,000 presence records of benthic genera for the North Sea, to identify environmental (bed shear stress, sediment grain size, temperature) and anthropogenic parameters (trawling effort) driving benthic community composition over a 21‐year period. We applied a Gradient Forest analysis, based on Random Forests, to estimate the locations and importance of thresholds where small cumulative increases in the predictors drive a much greater change in genus composition than would be expected from linear effects. Shear stress was the most important predictor of benthic community composition. Trawling effort, temperature gradients and sediment grain size were of intermediate importance. This corroborates that current and wave effects (typically associated with seabed substrate types) are primary determinants of benthic communities. Our results suggest that a genus composition threshold for both infauna and epifaunal benthic communities is crossed when the seafloor is trawled as little as once every 4 years. Higher trawling levels corresponded with gradual compositional change without obvious thresholds, which would be consistent with chronic fishing in the North Sea over the last two centuries having caused persistent, long‐term changes in ecosystem structure and functioning. This was corroborated by the large‐scale spatial patterns of benthic community composition undergoing limited temporal changes during the 21‐year study period. Synthesis and applications. Although well established in theory, threshold effects are poorly validated in the field. We generated new information on multi‐organism responses to environmental change at the scale of a continental shelf ecosystem and over a multi‐decadal time period. This will help pure and applied scientists better understand the conditions under which community thresholds are crossed and provide environmental managers with empirical evidence that is expected to reduce uncertainty regarding decisions on the protection and sustainable use of the marine environment. Resumen Ecologistas y administradores medioambientales necesitan entender el tipo de comunidades que emergen en respuesta a los efectos de las acciones humanas en los ecosistemas, en un contexto de cambio natural. Es bien sabido que tanto los efectos naturales como los antropogénicos impactan las distribuciones de organismos; sin embargo, a menudo no está claro dónde se producen cambios importantes en la composición de las comunidades en un gradiente de variaciones de factores ambientales y antropogénicos. Realizamos un análisis de ‘big data’, con más de 175,000 registros de presencia de géneros bentónicos en el Mar del Norte, para identificar parámetros naturales (tensión de cizalladura del fondo marino, tamaño de partículas del sedimento, temperatura) y antropogénicos (intensidad de pesca de arrastre) que influencian la composición de la comunidad bentónica en un período de 21 años. Aplicamos un análisis de Gradiente de Bosques Aleatorios (‘Gradient Forests’), una técnica basada en Bosques Aleatorios, para estimar la localización e importancia de los umbrales de transición donde pequeñas variaciones de los predictores provocan cambios mucho mayores en la composición de géneros de las comunidades bentónicas de lo que podía esperarse por efectos lineales. La tensión de cizalladura es el predictor más importante de la composición de la comunidad bentónica. La intensidad de pesca de arrastre, la temperatura y el tamaño de partículas del sedimento tienen importancia intermedia. Esto corrobora que los efectos de la corriente y las olas (muy relacionados con los tipos de sustrato del fondo marino) son determinantes primarios de las comunidades bentónicas. Nuestros resultados sugieren que se producen cambios importantes de composición de géneros bentónicos tanto para las comunidades epifaunales como infaunales cuando el fondo marino es sometido a pesca de arrastre tan poco como una vez cada cuatro años. Niveles más altos de pesca de arrastre provocan un cambio gradual de composición sin umbrales obvios, consistente con la hipótesis de que la estructura y funcionamiento de los ecosistemas bentónicos en el Mar del Norte han sufrido cambios persistentes debido a los niveles crónicos de pesca de arrastre que han experimentado durante los dos últimos siglos. Esto es corroborado por las limitadas variaciones en la distribución espacial a gran escala de la composición de comunidades bentónica durante los 21 años del período estudiado. Síntesis y aplicaciones. Aunque bien establecidos en la teoría, hay pocos datos de campo que validen la existencia de umbrales de transición de ecosistemas. En este trabajo analizamos las respuestas de múltiples organismos al cambio ambiental a la escala de una plataforma continental y durante un período de varias décadas. Nuestros resultados ayudarán a científicos teóricos y aplicados a comprender mejor las condiciones bajo las cuales se cruzan los umbrales de transición de las comunidades bentónicas, y proporcionarán a los administradores ambientales datos empíricos para apoyar decisiones sobre la protección y el uso sostenible del medio marino. Although well established in theory, threshold effects are poorly validated in the field. We generated new information on multi‐organism responses to environmental change at the scale of a continental shelf ecosystem and over a multi‐decadal time period. This will help pure and applied scientists better understand the conditions under which community thresholds are crossed and provide environmental managers with empirical evidence that is expected to reduce uncertainty regarding decisions on the protection and sustainable use of the marine environment.